Políticas sociales y complejidad: un enfoque desde el análisis de redes (2010)
The following is a trial of research on socialreview on social policies from a viewpoint of the theory of complexity and how they contribute to the analysis of social networks. Part of a theoretical lift to culminate with a proposal to enable understanding of issues related to the social, political and cultural situation of social networks, as well as in the analysis of the Colombian social policies, based on examples and applications in this regard. The efforts of the article consists of developing the theory and put it into practice. In this case, a schema or comprehensive plan for attention to the problem of displacement in Colombia.For this reason, the work moves within the line of sociology, pedagogy, politics, and anthropology